The One21 Technique: An Individualized Treatment for Glabellar Lines Based on Clinical and Anatomical Landmarks - de Sanctis Pecora C; Pinheiro MVB; Ventura Ferreira K; Jacobino de Barros Nunes G; Miot HA (Dove Medical Press, 2021)
Carla de Sanctis Pecora,1 Maria Valéria Bussamara Pinheiro,1 Karin Ventura Ferreira,1 Gisele Jacobino de Barros Nunes,1 Hélio Amante Miot2 1Dermatologie - Clinica, Cirurgia, Cosmiatria e Laser, São Paulo, SP, Brazil; 2Departamento de Dermatologia da FMB-Unesp, Botucatu, SP, BrazilCorrespondence: Carla de Sanctis Pecora Dermatologie - Clinica, CirurgiaCosmiatria e Laser, Avenida Ibirapuera, 2907, Conj 901, São Paulo, SP, CEP 04029-200, BrazilTel/Fax +551150420872Email carla@dermatologie.com.brPurpose: Botulinum toxin type A is an effective treatment for glabellar dynamic wrinkles. As the muscular group involved in the contraction of the glabella varies among people, individualized treatment can achieve optimal results. This study evaluates a customized assessment for the treatment of glabellar lines with Incobotulinumtoxin-A, leading to an individualized points distribution and dosage.Patients and Methods: A single-center, evaluator-blinded, therapeutic cohort study enrolled 130 women with moderate or severe glabellar wrinkles. They underwent Incobotulinumtoxin-A injection following the standard 5-point injection at the glabellar muscles (n = 65) or an individualized assessment and scheme treatment based on anatomical references of contraction, the One21 technique (n = 65). All the patients were photographed under maximum contraction before treatment (T0) and after 4 weeks (T28). The photos were randomly assessed by two blinded, experienced raters to consensually grade the severity according to the Merz Aesthetics Scales (MAS). The primary clinical efficacy was defined as a 2-point reduction in the MAS score, on Day 28.Results: The groups were homogeneous regarding age, phototype, and baseline MAS scores. On Day 28 (T28), 64 (98.5%) patients from the One21 group and 52 (80%) from the 5-point group reduced the MAS score by at least two points (p < 0.01). When adjusted by age and phototype, both groups reduced the MAS score at T28 (p < 0.01); nevertheless, patients from the One21 group significantly performed better (p < 0.01), with a much higher rate response rate at T28, in comparison to the 5-point group. Of patients enrolled in the 5-point group, 83.1% utilized muscle groups other than the procerus and corrugator in glabellar wrinkle formation, and 17 (24.6%) presented asymmetrical contraction. Patients from the 5-point group with glabellar asymmetry and those who utilized the frontalis and orbicularis presented inferior performance (p < 0.05), reinforcing the importance of an individualized assessment and treatment plan.Conclusion: The One21 technique yielded better results than the standard 5-point treatment in reducing glabellar dynamic lines with Incobotulinumtoxin-A, especially for asymmetric lines of the glabella or the involvement of muscle groups other than the procerus and corrugator.Keywords: botulinum toxin type A, incobotulinumtoxinA, evaluation studies as a topic, face, muscle contraction, treatment, glabella